Words as competitive assets: Linguistic strategies in Marrakech’s online reviews and promotional texts - Ed-dali, Rachid; El Gourari , Wyssal (American Journal of STEM Education, 2026)
This mixed-methods study examines linguistic features in Marrakech’s digital tourism discourse through analysis of 2,000 English-language reviews from TripAdvisor and Google (2022-2024) alongside official marketing texts. Using VADER sentiment analysis, thematic coding, and statistical techniques, the research explores associations between language use and tourist perceptions. While narrative reviews with cultural terminology ("riad," "medina") showed statistically higher ratings (4.3 vs 3.9/5, p < .001), linguistic features explained only 5-15% of rating variance. Demographic patterns emerged, with solo female travelers expressing 15% lower positivity, likely reflecting safety concerns rather than linguistic preferences. Marketing language showed modest correlations with engagement metrics, though causality cannot be established from this cross-sectional design. The findings challenge assumptions about linguistic optimization in tourism marketing, revealing that language plays a more limited role than commonly believed, with 85-95% of tourist satisfaction determined by non-linguistic factors. The study’s English-only focus and correlational design limit generalizability, suggesting a need for experimental, multilingual research to better understand language’s actual impact on tourism outcomes.